The influence of thermal annealing on structural properties of Ni nanotubes. (July 2018) - Kozlovskiy, A.L.; Shlimas, D.I.; Kenzhina, I.E.; Zdorovets, M.V.
Abstract: The paper presents the results of studying the structural properties of Ni nanotubes affected by thermal annealing. Scanning electron microscopy, X-ray phase analysis and energy dispersive analysis were used to investigate the microstructure. An increase in the annealing temperature is found to lead to a change in the main crystallographic characteristics (unit cell parameter, crystallite size) and the appearance of new phases in the structure. The change in microarrays in the structure as a result of thermal annealing is of a two-stage nature: the first stage is characterized by an improvement in the crystal structure as a result of annealing defects; the second stage is characterized by an increase in micro-displacements in the crystal structure due to the appearance of two phases-the nickel oxide compound NiO2 and γ-Ni, whose contribution increases with the annealing temperature. At the same time, the formation of new phases in the crystal structure leads to a partial amorphization of the structure and the formation of outgrowths on tubes surface. The obtained knowledge can be applied to supplement the theory of thermal stability of nanostructures, as well as to assess their applicability in modern materials science. Highlights: The results of studying the changes in structural properties of Ni nanotubes influenced by thermal annealing. As scanning methods, scanning electron microscopy, X-ray phase analysis were used. The annealing temperature is found to lead to a change in main crystallographic characteristics and the appearance of new phases in the structure. The obtained knowledge can be applied to supplement the theory of thermal stability of nanostructures.